2014
DOI: 10.1088/0067-0049/214/2/15
|View full text |Cite
|
Sign up to set email alerts
|

A HIGHLY CONSISTENT FRAMEWORK FOR THE EVOLUTION OF THE STAR-FORMING “MAIN SEQUENCE” FROM z ∼ 0-6

Abstract: Using a compilation of 25 studies from the literature, we investigate the evolution of the star-forming galaxy (SFG) Main Sequence (MS) in stellar mass and star formation rate (SFR) out to z ∼ 6. After converting all observations to a common set of calibrations, we find a remarkable consensus among MS observations (∼ 0.1 dex 1σ interpublication scatter). By fitting for time evolution of the MS in bins of constant mass, we deconvolve the observed scatter about the MS within each observed redshift bins. After ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

243
2,119
24
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,494 publications
(2,432 citation statements)
references
References 244 publications
243
2,119
24
1
Order By: Relevance
“…Curves for the Schreiber et al (2015) relations come from their parameterization evaluated at the central redshift of each bin shown here (see their Section 4.1). Similarly, the curves for Speagle et al (2014) correspond to parameterizations from their Table 9: "All" and "Mixed" for the all-and star-forming galaxy samples shown here. We also note that the redshift bins of the Karim et al (2011) relations are different than those indicated at the top: 0.6 < z < 0.8, 1.0 < z < 1.2, 1.6 < z < 2.0, 2.0 < z < 2.5, and 2.5 < z < 3.0 respectively.…”
Section: Comparison To Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Curves for the Schreiber et al (2015) relations come from their parameterization evaluated at the central redshift of each bin shown here (see their Section 4.1). Similarly, the curves for Speagle et al (2014) correspond to parameterizations from their Table 9: "All" and "Mixed" for the all-and star-forming galaxy samples shown here. We also note that the redshift bins of the Karim et al (2011) relations are different than those indicated at the top: 0.6 < z < 0.8, 1.0 < z < 1.2, 1.6 < z < 2.0, 2.0 < z < 2.5, and 2.5 < z < 3.0 respectively.…”
Section: Comparison To Literaturementioning
confidence: 99%
“…Another type of lookback study involves using the observed correlation between stellar mass and star formation rate, hereafter referred to as the SFR-M * relation (e.g., Brinchmann et al 2004;Noeske et al 2007;Gilbank et al 2011;Whitaker et al 2012;Speagle et al 2014). By tracing along this evolving star formation sequence it is possible to predict how galaxies should evolve due to star formation (e.g., Leitner 2012;Speagle et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are randomly selected to be massive galaxies that lie below the star-forming main-sequence relation with different separations from the main sequence, ΔsSFR, defined as the offset in log(sSFR) relative to the mainsequence value (i.e., log(sSFR)-log(sSFR MS )). Previous studies have revealed significant differences in the slope and normalization of the main sequence (e.g., see Speagle et al 2014). The selection of the star-forming population, the method determining the star formation rate and stellar mass, as well as the IMF, have a strong effect in determining the properties of the main sequence.…”
Section: Manga Targetsmentioning
confidence: 99%
“…The IR-bright QG candidates have similar or higher SFR H compared to SFGs, and are significantly higher than the IR-faint counterparts. For comparison, the SFR-M å measured in Speagle et al (2014) is plotted as gray lines, with the 1−3× observed dispersion (σ SFR =0.3) shown as dark-to-light shades. IR-faint QG candidates have SFRs at least 2-3 dispersions (0.6-0.9 dex) below those of SFGs out to z∼2, and at z=2-3 the difference is smaller.…”
Section: Estimations Of Ir Luminosities and Sfrsmentioning
confidence: 99%